"Lantern-Shaped" Platinum(III) Complexes with Axially Bound 9-Ethylguanine or 1-Methylcytosine (L) of General Formula [Pt2{HN=C(But)O}4L2](NO3)2. (8th June 2010) - Pacifico, Concetta; Intini, Francesco Paolo; Nushi, Fiorentin; Natile, Giovanni
Abstract : The synthesis, NMR characterization, and X-ray crystallography of "lantern-shaped" platinum(III) complexes with four pivaloamidate bridging ligands and two 9-ethylguanines (9-EtG) or 1-methylcytosines (1-MeC) in axial positions are reported: cis- N 2 O 2 -[Pt2 {HN=C(Bu t )O}4 (9-EtG)2 ](NO3 )2 and cis -N 2 O 2 -[Pt2 {HN=C(Bu t )O}4 (1-MeC)2 ](NO3 )2 . The last complex is, to the best of our knowledge, the first dinuclear compound of platinum(III) with axially bound 1-MeC.